ANTIPHOSPHOLIPID PATTERN AS A PART OF THE PATHOGENESIS OF MYOCARDIAL INFARCTION - Burdeina, L.V.; Nazarova, M.S.; Kuzminova, N.V.; Lozinsky, S.E.; Khomenko, V.M.; Shvets, L.V.; Kniazkova, I.I. (World of Medicine and Biology, 2025)
A systematic review of the international literature was conducted using the PubMed platform. The purpose of the study was to obtain information about the role of antiphospholipid syndrome in the pathogenesis of myocardial infarction. Acute myocardial infarction is often the first manifestation of antiphospholipid syndrome in young patients. Young patients under 50 years of age without additional risk factors for cardiovascular disease or atherosclerosis of the coronary arteries with recurrent cardiovascular events, including myocardial infarction, should be screened for antiphospholipid syndrome.